Desing and development of new textil materials for insulacion and acoustic - Inche Mitma, Jorge Luis (2010)
This article treats the following problem How can we reduce the noise emission in a room?; to answer to this question it has been considered to absorbent materials like Glass Wool and Nappe Textile by mean a construction of a board acoustic prototype they put under an experiment following the instructions of the UNE-EN 20354 norm and being obtained satisfactory results to both materials, but in especial to the Glass Wool.